PRACTICAL USE OF THE WEBQUEST AS A TOOL OF FUTURE LAWYERS’ PROFESSIONALLY ORIENTED ENGLISH LANGUAGE SPEAKING COMPETENCE DEVELOPMENT - Diachkova, Iana O. (Educological discourse, 2014)
The article introduces a practical development of the WebQuest for future lawyers devoted to the topic "Fraud" and discloses methodological potential of this teaching tool for professionally oriented English language speaking competence development. The definition of the WebQuest as a teaching tool for future specialists’ professionally oriented English language speaking competence development is given. The result of the WebQuest is determined. The role of the teacher within the WebQuest is noted and the results of the teacher’s operations for the organization of students’ activity are disclosed. The realization of each structural component of the WebQuest and its goals in the context of future lawyers’ leading learning speaking objective’s implementation are shown practically.